Cultural Identity in the Book of Tafsir Raudhatul Irfan fi Ma'rifatil Qur'an by K.H. Ahmad Sanusi - Hidayatulloh, Taufik; Hajam, Hajam; Saumantri, Theguh; Abdillah, Abdillah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The tafsir (Qur’anic commentary) is one of the essential tools for explaining and deepening the understanding of the teachings of the Qur’an within the community. Besides serving as a religious instrument, tafsir often reflects cultural richness by integrating Islamic aspects with local cultural values. This study aims to explore how the cultural identity of the Sundanese people is reflected in the Tafsir Raudhatul Irfan fi Ma’rifatil Qur’an, written by K.H. Ahmad Sanusi from Sukabumi. The research method used is descriptive-analytical with a qualitative approach. The findings of this study indicate that the cultural identity in the Tafsir Raudhatul Irfan is evident in several aspects of local wisdom, particularly in the field of language. The Sundanese language used in this tafsir is the daily language of the mufassir (commentator). Thus, the writing of this tafsir was primarily intended for the students in Islamic boarding schools and the Sundanese community who understand the language rather than for a broader audience. Furthermore, the cultural identity is also reflected in the writing system, where the mufassir utilizes the Pegon script to convey his tafsir. The Pegon script, which is a writing system that uses Arabic characters for the Sundanese, Javanese, and Madurese languages, is employed in this tafsir as a means to preserve and maintain local literary traditions while still conveying Islamic teachings.